Comparison of Digestive Enzyme Activities and Expression of Small Intestinal Transporter Genes in Jinhua and Landrace Pigs - Liu, Xiuting; Lyu, Wentao; Liu, Lei; Lv, Kaikai; Zheng, Fen; Wang, Yuanxia; Chen, Jinggang; Dai, Bing; Yang, Hua; Xiao, Yingping (Frontiers in Physiology, 2021)
The objective of this study was to investigate differences in the digestive enzyme activities and expression of intestinal nutrient transporters in Jinhua and Landrace pigs to explore the potential breed-specific relationship with digestion and absorption abilities. We compared and analyzed the activities of trypsin, chymotrypsin, amylase, maltase, sucrase and lipase in the pancreas and the small intestine mucosa, as well as their contents of these two species. Furthermore, differences in PepT1, GLUT2, SGLT1, FABP1, FABP2 and FABP4 expression levels in the small intestine were assessed. Four main results were observed. First, compared with Landrace pigs, the trypsin activity in the pancreatic tissue of Jinhua pigs was higher (P<0.05), but it was significantly lower in the small intestine (P<0.05), except for in jejunal mucosa. In addition, the chymotrypsin activity in the small intestine was significantly higher (P<0.05), except for in jejunal mucosa and contents. Second, compared with Landrace pigs, the amylase activity in the small intestine of Jinhua pigs was significantly lower (P<0.05), except for in ileal mucosa, and the maltase activity in whole small intestine was significantly lower (P<0.05). In addition, the sucrase activity in the small intestine was significantly lower (P<0.05), except for in jejunal mucosa (P>0.05). Third, the lipase activity in the whole small intestine of Jinhua pigs was significantly higher than that in Landrace pigs (P<0.05). Fourth, the mRNA levels of the Pept1 and GLUT2 in duodenal, jejunal and ileal mucosa showed no significant difference between Jinhua and Landrace pigs (P>0.05), whereas SGLT1 in ileal mucosa was significantly lower in Jinhua pigs (P<0.01). The mRNA levels of FABP1, FABP2 and FABP4 in all small intestinal mucosa of Jinhua pigs were higher, of which FABP1 in jejunal and ileal mucosa showed extremely significant differences (P<0.01), FABP2 showed a significant difference in duodenal mucosa (P<0.05) and an extremely significant difference in ileal mucosa (P<0.01), and FABP4 showed an extremely significant difference in jejunal and ileal mucosa (P<0.01). These results indicate that there is a certain difference in the digestibility of intestinal nutrients between Jinhua and Landrace pigs, partially reflecting their differences in growth development and characteristics.